Self Medication’s Description of Skin Disease In Martapura Regional Community - Herningtyas Nautika Lingga; Difa Intannia (LPPM - Universitas Muhammadiyah Banjarmasin, 2021)
Skin disease is often occurs in wetland areas that can be treated with self-medication. This study aimed to describe skin disease’s self-medication in the community in the Martapura area. This study was a descriptive with a cross sectional design with respondents as many as 100 visitors to the Martapura Health Center who have experienced skin disorders or diseases. The instrument used was a questionnaire and the analysis carried out was univariate analysis. The results showed that the characteristics of the community who practiced self-medication were mostly in the age range of 25 - 60 years with the male gender, the latest high school education and self-employed work. Most places to live in densely populated neighborhoods. This study concluded that skin disease’s self-medication was carried out by the community is based on the reasons for doing self-medication because of time and previous experience, with the most places to buy drugs in pharmacies. The most common type of skin disease is a fungal infection with the drugs used are anti-fungal and other such as herbal medicines.